CircR2Cancer: a manually curated database of associations between circRNAs and cancers. (11th November 2020) - Lan, Wei; Zhu, Mingrui; Chen, Qingfeng; Chen, Baoshan; Liu, Jin; Li, Min; Chen, Yi-Ping Phoebe
Abstract: Accumulating evidences have shown that the deregulation of circRNA has close association with many human cancers. However, these experimental verified circRNA–cancer associations are not collected in any database. Here, we develop a manually curated database (circR2Cancer) that provides experimentally supported associations between circRNAs and cancers. The current version of the circR2Cancer contains 1439 associations between 1135 circRNAs and 82 cancers by extracting data from existing literatures and databases. In addition, circR2Cancer contains the information of cancer exacted from Disease Ontology and basic biological information of circRNAs from circBase. At the same time, circR2Cancer provides a simple and friendly interface for users to conveniently browse, search and download the data. It will be a useful and valuable resource for researchers to understanding the regulation mechanism of circRNA in cancers. Database URL: http://www.biobdlab.cn:8000